Prognostic Factors for Outcome in Localized Extremity Rhabdomyosarcoma. Pooled Analysis from Four International Cooperative Groups. Issue 12 (10th August 2015) - Oberlin, Odile; Rey, Annie; Brown, Kenneth L.B.; Bisogno, Gianni; Koscielniak, Ewa; Stevens, Michael C.G.; Hawkins, Douglas S.; Meyer, William H.; La, Trang H.; Carli, Modesto; Anderson, James R.
<x xml:space="preserve">Abstract</x> Background Extremity rhabdomyosarcomas do not always show satisfactory outcomes. We analyzed data from 643 patients treated in 14 studies conducted by European and North American groups between 1983 and 2004 to identify factors predictive of outcome. Procedure Clinical factors, including age; histology; site of primary (hand and foot vs. other); size; invasiveness (T stage); nodal involvement (N stage); and treatment factors, including post‐surgical group; chemotherapy type and duration; radiotherapy; and treatment (before or after 1995); were evaluated for impact on overall survival (OS). Results 5‐year OS were 67% (se 1.8). Multivariate analysis showed that lower OS correlated with age >3 years, T2 and N1 stage, incomplete initial surgery, treatment before 1995, and European cooperative group treatment. Patients with gross residual disease after initial incomplete resection/biopsy had similar outcomes in both continental groups. The better global survival of patients treated in American studies was accounted for by differences in outcome in the subset of those with grossly resected tumors (OS 86% [se 3] for COG patients vs. 68% [se 4] for European patients (P = 0.004)). When excluding chemotherapy duration from the model, analysis in this subset of patients showed that cooperative group (P = 0.001), site (P = 0.001), and T stage (P = 0.05) were all significant. However, after adding duration of chemotherapy (≥27 weeks) to the model, only primary site remained significant (P = 0.006). Conclusion This meta‐analysis confirms the role of many established prognostic factors but identifies for the first time that chemotherapy duration may have an impact on outcome in patients with grossly resected tumors. Pediatr Blood Cancer © 2015 Wiley Periodicals, Inc.